Assessment of the Jugular Foramen in the Posterior Cranial Fossa of Nigerian Adult Skulls - Ibinabo Fubara, Bob-Manuel; Ogoun, Timipa Richard; Blessing, Martins (International Journal of Health Sciences, 2022)
Unique contribution to theory, practice and policy: The knowledge of the morphometry of this foramen is important for forensic scientists, anthropologists and neurosurgeons. It could be concluded that the data provided in this study is important for advancement of Anatomical Science in Nigeria.